A COMPARATIVE ANALYSIS OF NEGATION MARKERS IN URDU AND ENGLISH SERIAL VERB CONSTRUCTIONS (Al-Aasar, 2025)
Serial Verb Constructions (SVCs) are an integral syntactic phenomenon that involves the integration of multiple verbs in a single clause without conjunctions. These SVCs provide insights into the intricacies of verb usage and essential features of syntactic relationships. The negation process reveals and gives insight into various fundamentally crucial features of a language. This study gives a comparative analysis of SVC negation in Urdu and English, focusing on the syntactic mechanisms used in relevance to the position of negation markers in them incorporating a theoretical framework based on Chomsky’s Minimalist Program. The study identifies the significant differences between Urdu and English by discriminating the key patterns and variations involved in negation in SVCs through qualitative analysis. The previous studies have highlighted the negation in SVCs but they have not described the varient negation particles for plural subject arguments i.e. nəhĩ (not) in Urdu. The findings of this study suggest the existence of differences with respect to the positioning of the negators. Urdu and English, both languages exhibit the existence of SVCs, just like many other languages of the world but with some distinct properties. Urdu negation precedes the projection of verb or the entire SVC while English negation uses auxiliary verbs in SVCs. This study contributes to the broader spectrum of understanding the negations in SVCs and provides valuable insights into comparative linguistic study for enhancing the existing body of knowledge pertaining to the syntaxes of Urdu and English.